Proceedings of the 2005 International Cross-Disciplinary Workshop on Web Accessibility (W4A) - W4A '05 2005
DOI: 10.1145/1061811.1061819
|View full text |Cite
|
Sign up to set email alerts
|

Web composition with WCAG in mind

Abstract: Accessibility should be a part of the Web design process instead of being a post-design repair process. Thus, it should be more integrated within the internal authoring tools' mechanism of generating new accessible Web contents. Web pages are usually composed of small pieces of HTML code which, dynamically nested and combined, generate full Web pages. This Web composition, specially when creating Web pages from data extracted from heterogeneous or external sources, should have accessibility into account in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The work by Centeno et al [5] presents the set of rules that, in a Web composition process, a design tool must follow in order to create accessible Web pages. These rules are formalized with W3C standards like XPath 5 and XQuery 6 expressions, defining conditions to be met in order to guarantee that Accessible chunks of Web pages are safely composed into a page that also turns out to be Accessible.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…The work by Centeno et al [5] presents the set of rules that, in a Web composition process, a design tool must follow in order to create accessible Web pages. These rules are formalized with W3C standards like XPath 5 and XQuery 6 expressions, defining conditions to be met in order to guarantee that Accessible chunks of Web pages are safely composed into a page that also turns out to be Accessible.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Rosmaita [30] offered an ''accessibility first'' approach to web design; he proposed an accessibility first pedagogy for web design. Centeno et al [11] also argued that web accessibility needed to be included in the design process rather than be a post-design process. They also showed that designers cannot rely solely on authoring and design tools.…”
Section: Achieving Web Accessibilitymentioning
confidence: 99%
“…Studies by Centeno et al [11] and Law et al [23] showed that accessibility is part of the web design process. Thus, the district webmaster must be part of the committee early on.…”
Section: A General Approach To Web Designmentioning
confidence: 99%
“…With regard to Web pages composed of autonomous components, enforcing and verifying quality guidelines at development time is rather sophisticated. Regarding for example accessibility aspects, this is due to the fact that the composition of components which are themselves accessible is not necessarily accessible [11].…”
Section: Data Presentation -The 'Rendermarkup' Activitymentioning
confidence: 99%